Uslub al-Fi’l al-Mudhari’ fi Khutbah al-Jum’ah li al-Syaikh Abd al-Majid ibn Abd al-Hamid: The Style of the Present Tense Verb (Fi‘l al-Muḍāri‘) in the Friday Sermons of Sheikh ‘Abd al-Majīd ibn ‘Abd al-Ḥamīd - Hamdy, Mohammad Zainal; Masdur, Masdur (Critical Review of English-Arabic World Journal, 2022)
الخطبة في الاصطلاح الشرعي هي الخطاب الذي يُلقى على المنابر يوم الجمعة بقصد الحثّ على الخير والترغيب فيه، وصرف الناس عن الشرّ ودواعيه، وتنبيههم إلى أحوالهم وواقع أمورهم بما يقتضيه الشرع. وقد عرض الباحث في هذا البحث مسألة مهمة، وهي أسلوب التعبير بالفعل المضارع في خطب الجمعة للشيخ عبد المجيد بن عبد الحميد، أما منهج البحث المتّبع في هذا البحث فهو بعض أنواع البحث المكتبي (الدراسات المكتبية) من خلال الرجوع إلى أنواعٍ من الكتب والمراجع. وبعد أن نظر الباحث في خطب الجمعة، وجد فيها اثنين وعشرين فعلاً مضارعاً، تتكوّن من ثمانية أفعال مضارعة مرفوعة بعلامة ظاهرة، وفعل واحد مضارع مرفوع بعلامة مقدّرة على الألف، وفعل واحد مضارع مرفوع بعلامة مقدّرة على الواو، وعشرة أفعال مضارعة منصوبة، وفعل واحد مضارع مجزوم بالسكون المقدّر على الألف، وفعل واحد مضارع مجزوم بالسكون المقدّر على الياء، وفعلين مضارعين اتّصلا بضمير جماعة مرفوع، وفعل واحد مضارع اتّصل بضمير جماعة الجمع. The Friday sermon in terms of legal terminology is (the sermon delivered on the pulpits on Friday with the intention of encouraging people to do good, encouraging them to do it, distracting them from evil and its motives, and making them aware of their conditions and the reality of their affairs, as required by the law. In this research, the researcher presented an important matter, which is the method of expressing the present tense verb in the Friday sermon of Sheikh Abdul Majeed bin Abdul Hamid, and the research method of this research is some of the types of library research. types of books. After the researcher looked at the Friday sermon, he found twenty-two in it, which consisted of 8 present tense parsing with a pronounced vowel, and from 1 parsing of the present tense with a vowel estimated in a thousand, and from 1 parsing of the present tense with a vowel estimated by wu, and from 10 parsing of the present tense verb with a vowel, And from 1 the parsing of the present verb is compounded by the sukoon estimated by a thousand, and from 1 the expression of the present tense verb is compounded by the sukoon estimated by ya. And from 2 the articulation of the present verb if it is called by a nominative plural pronoun, and from 1 the articulation of the present verb if it is called by a plural pronoun that is plural.